When a human gives birth to a raven : rabbis and the reproduction of species - Neis, Rachel (University of California Press, 2023)
"This book investigates rabbinic treatises relating to animals, humans, and other lifeforms. Through an original analysis of creaturely generation and species classification by late ancient Palestinian rabbis and other thinkers in the Roman empire, Rafael Rachel Neis shows how rabbis blurred the lines between the human and other beings. This they did even as they were intent on classifying creatures and delineating the contours of the human. Recognizing that life proliferates via multiple mechanisms beyond sexual copulation between two heterosexual 'male' and 'female' individuals of the same species, the rabbis produced intricate alternatives. This expansive view of generation included humans. Likewise, in parsing the variety of creatures, the rabbis attended to the overlaps and resemblances across seemingly distinct species, upsetting in turn unmitigated claims of human distinctiveness. Intervening in conversations in animal studies, queer theory, trans theory, and feminist science studies, When a Human Gives Birth to a Raven provincializes sacrosanct ideals of reproduction in favor of a broader range of generation, kinship, and species offering powerful historical alternatives to the paradigms associated with so-called traditional ideas"--